Sensitivity and responses of chloroplasts to salt stress in plants - Wang, Xuemei; Chen, Zengting; Sui, Na (Frontiers in Plant Science, 2024)
Chloroplast, the site for photosynthesis and various biochemical reactions, is subject to many environmental stresses including salt stress, which affects chloroplast structure, photosynthetic processes, osmotic balance, ROS homeostasis, and so on. The maintenance of normal chloroplast function is essential for the survival of plants. Plants have developed different mechanisms to cope with salt-induced toxicity on chloroplasts to ensure the normal function of chloroplasts. The salt tolerance mechanism is complex and varies with plant species, so many aspects of these mechanisms are not entirely clear yet. In this review, we explore the effect of salinity on chloroplast structure and function, and discuss the adaptive mechanisms by which chloroplasts respond to salt stress. Understanding the sensitivity and responses of chloroplasts to salt stress will help us understand the important role of chloroplasts in plant salt stress adaptation and lay the foundation for enhancing plant salt tolerance.